Inorganic temperature core box, binder and preparation method thereof

Through the introduction of silicon microfream powder and other ingredients in the use of adhesives, the problem of harmful gases and carbon emissions during the casting process of existing adhesives is solved. The cleanliness and size accuracy of the casting is improved, which improves production efficiency and economic benefits.

CN119346794AActive Publication Date: 2025-01-24JINAN SHENGQUAN GRP SHARE HLDG CO LTD +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411440365.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-24
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The existing casting adhesives will generate harmful gases and a large amount of carbon emissions in the core making and casting process, and it is difficult to improve the fluidity of the mixture between silica sand and binder, affecting the finish and dimensional accuracy of the castings.

Method used

An inorganic warm core box binder formula is used, including silica sand, component A and component B. Component B contains passivated silica powder, graphite powder, zircon powder, mullite particles and lignosulfonic acid Salt, through these components, reduces the viscosity and frictional resistance of the binder and silica sand mixture, and improves fluidity.

Benefits of technology

It improves the fluidity of the mixture of silica sand and binder, improves the stability and compactness of the sand mold surface, enhances the smoothness and dimensional accuracy of the casting surface, and reduces the problems of inclusions, pores and blisters, thereby improving the production of castings. efficiency and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005087168440000201
    Figure BDA0005087168440000201
  • Figure BDA0005087168440000211
    Figure BDA0005087168440000211
Patent Text Reader

Abstract

The invention discloses an inorganic temperature core box, a binder and a preparation method of the inorganic temperature core box, the inorganic temperature core box comprises 100 parts by weight of silica sand and 2.2-3.3 parts by weight of the binder, the binder comprises a component A and a component B, and the component B comprises passivated silica powder. According to the inorganic temperature core box provided by the invention, the component B can effectively improve the flowability of the mixture of the silica sand and the binder. The fluidity is improved, so that the stability and compactness of the surface of the sand mold can be improved, and the core making effect of a complex sand core can be improved; the smoothness and the size precision of the surface of the casting can be improved, and the problems of inclusion, air holes, sand holes and the like are reduced, so that the production efficiency of the casting and the economic benefits of casting manufacturers are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of adhesives for casting, and in particular to an inorganic warm core box, an adhesive and a preparation method thereof. Background Art

[0002] Casting binders can be divided into organic and inorganic types. Organic binders are widely used, but they will produce toxic gases such as furan, dioxin, benzene, phenol, etc. during core making and casting, and will also produce a large amount of carbon emissions. Inorganic binders have the advantages of being green and environmentally friendly, and have always been the development direction of green casting that has attracted much attention. Among them, the inorganic warm core box process has the advantages of low heating temperature, low energy consumption, and environmental friendliness. Since its appearance, it has received widespread attention and application in the automotive and other fields.

[0003] A modified water glass sand warm core box core making process is disclosed in the Chinese invention patent with the authorization announcement number of CN 100531959C. It uses nano silicon powder, coal slag powder and the like as modifiers. The warm core box process can improve the working environment and reduce the deformation of the core box. A warm core box binder and a preparation method are disclosed in the Chinese invention patent application with the publication number of CN 114406181 A. Hydrophilic decontamination fillers, anticorrosive wear-resistant fillers and aluminosilicate refractory materials are added to the raw materials. The formula can enhance the corrosion resistance and wear resistance of the binder and improve the adsorption of magnetic impurities in the sand particles. A two-component water-soluble binder for warm core box method for casting and its use method are disclosed in the Chinese invention patent application with the publication number of CN 115533021 A. The improved components can improve the bonding performance and application performance, improve the collapsibility, and improve the strength of the sand core. A curing agent for casting water glass is disclosed in the Chinese invention patent with the authorization announcement number of CN 108393430 B. It uses an ester composite ZrSiO4 thermally decomposed amorphous silicon dioxide as the powder component of the warm core box binder. The composite has the advantages of strong bonding, long shelf life, and easy operation. None of the above patent documents improve the fluidity of the binder and silica sand mixture. Summary of the invention

[0004] In order to solve the above problems, the present application provides an inorganic core warming box, in which component B can effectively improve the fluidity of the mixture of silica sand and binder. The improvement of fluidity can improve the stability and compactness of the sand mold surface, and can improve the core making effect of complex sand cores; it can increase the surface finish and dimensional accuracy of the casting, reduce inclusions, pores, sand holes and other problems, thereby improving the production efficiency of castings and the economic benefits of foundries.

[0005] The present application provides an inorganic warm core box, comprising 100 parts (by weight percentage) of silica sand and 2.2-3.3 parts of a binder, wherein the binder comprises a component A and a component B, and the component B comprises passivated silicon powder.

[0006] Furthermore, the mass ratio of component A to component B is (1.6-2.2):(0.6-1.1).

[0007] Furthermore, the particle size of the passivated microsilica powder is 5-100 μm, preferably 30-75 μm.

[0008] Furthermore, the specific surface area of ​​the passivated microsilica powder is 0.1-2m 2 / g.

[0009] Furthermore, the content of silicon dioxide in the passivated microsilica powder is 90-99wt%.

[0010] Furthermore, the B component includes 20-75wt% of passivated microsilica powder, 5-10wt% of graphite powder, 5-20wt% of zircon powder, 5-25wt% of mullite particles and 1-10wt% of lignin sulfonate.

[0011] Furthermore, the lignin sulfonate is one of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate; or

[0012] The mullite particles are artificial sand spherical particles with an aluminum oxide content of greater than or equal to 60wt%.

[0013] Further, the D50 particle size of the mullite particles is 30-100 μm; and / or

[0014] The D50 particle size of the graphite powder is 30-100 μm; and / or

[0015] The D50 particle size of the zircon powder is 30-100 μm.

[0016] Furthermore, the component A is prepared according to a formula of 25-40wt% sodium silicate, 0.5-2wt% potassium hydroxide, 0.5-2wt% sodium aluminate, 2-10wt% silica sol and the balance being deionized water.

[0017] The present application also provides a method for preparing the aforementioned inorganic warm core box, comprising the following steps:

[0018] Put 100 parts by weight of silica sand into a sand mixer, add a certain proportion of binder component A and binder component B, mix, and put the mixed molding sand into the sand shooting bucket of a core shooting machine to make cores.

[0019] The present application also provides a binder, comprising a component A and a component B, wherein the component B contains passivated silicon powder.

[0020] Furthermore, the component A comprises 25-40wt% sodium silicate, 0.5-2wt% potassium hydroxide, 0.5-2wt% sodium aluminate, 2-10wt% silica sol, and the balance is deionized water;

[0021] The B component includes 20-75wt% of passivated microsilica powder, 5-10wt% of graphite powder, 5-20wt% of zircon powder, 5-25wt% of mullite particles and 1-10wt% of lignin sulfonate.

[0022] Furthermore, the lignin sulfonate is one of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate; or

[0023] The mullite particles are artificial sand spherical particles with an aluminum oxide content of greater than or equal to 60wt%.

[0024] Further, the D50 particle size of the mullite particles is 30-100 μm; and / or

[0025] The D50 particle size of the graphite powder is 30-100 μm; and / or

[0026] The D50 particle size of the zircon powder is 30-100 μm.

[0027] Furthermore, the particle size of the passivated microsilica powder is 5-100 μm, preferably 30-75 μm.

[0028] Furthermore, the specific surface area of ​​the passivated microsilica powder is 0.1-2m 2 / g.

[0029] Furthermore, the content of silicon dioxide in the passivated microsilica powder is 90-99wt%.

[0030] The present application also provides a method for preparing a binder, comprising the following steps:

[0031] Preparation of component A: Prepare component A according to a formula of 25-40wt% sodium silicate, 0.5-2wt% potassium hydroxide, 0.5-2wt% sodium aluminate, 2-10wt% silica sol and the balance being deionized water;

[0032] Preparation of component B: Prepare component B according to the formula of 20-75wt% of passivated microsilica powder, 5-10wt% of graphite powder, 5-20wt% of zircon powder, 5-25wt% of mullite particles and 1-10wt% of lignin sulfonate.

[0033] Furthermore, the adhesive prepared by the preparation method of the present application is the aforementioned adhesive.

[0034] The inorganic core warming box described in the present application, component B can effectively improve the fluidity of the mixture of silica sand and binder. The improvement of fluidity can improve the stability and compactness of the sand mold surface, and can improve the core making effect of complex sand cores; it can increase the surface finish and dimensional accuracy of the casting, reduce inclusions, pores, sand holes and other problems, thereby improving the production efficiency of castings and the economic benefits of foundries.

[0035] The B component of the binder of the present application can reduce the viscosity and friction resistance of the binder and silica sand mixture, thereby effectively improving its fluidity in use. DETAILED DESCRIPTION

[0036] The following is a description of the exemplary embodiments of the present application, including various details of the embodiments of the present application to facilitate understanding, which should be considered as merely exemplary. Therefore, it should be recognized by those of ordinary skill in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. Similarly, for the sake of clarity and conciseness, the description of well-known functions and structures is omitted in the following description.

[0037] The present application provides an inorganic warm core box, comprising 100 parts (by weight percentage) of silica sand and 2.2-3.3 parts of a binder, wherein the binder comprises a component A and a component B, and the component B comprises passivated silicon powder.

[0038] In some embodiments, the content of the silica sand is 100 parts by weight, and the content of the binder is 2.2-3 parts by weight.

[0039] Specifically, the content of the silica sand is 100 parts by weight, and the content of the binder can be 2.2 parts by weight, 2.3 parts by weight, 2.4 parts by weight, 2.5 parts by weight, 2.6 parts by weight, 2.7 parts by weight, 2.8 parts by weight, 2.9 parts by weight, 3 parts by weight, 3.1 parts by weight, 3.2 parts by weight, 3.3 parts by weight, etc.

[0040] The mass ratio of the silica sand to the component A is 100:(1.6-2.2), and the mass ratio of the silica sand to the component B is 100:(0.6-1.1). The appropriate ratio can obtain better sand core strength and sand core surface hardness. The increase in liquid components can allow the binder to better coat the surface of the sand particles, resulting in a thicker bonding film; however, too much liquid component will affect the disintegration, increase the possibility of pore formation, and also increase the economic cost of the foundry. Powder materials can provide hydroxyl-rich active microsilica powder, which can effectively react with liquid components and increase the modulus of water glass; however, too much powder material will accelerate the reaction speed, causing the silica sand mixture to dry out, and the usable time will be drastically shortened, seriously affecting the use effect of inorganic sand, and will also increase the economic cost of the foundry.

[0041] Specifically, the mass ratio of the silica sand to the component A can be 100:1.6, 100:1.7, 100:1.8, 100:1.9, 100:2.0, 100:2.1, 100:2.2, etc.

[0042] The mass ratio of the silica sand to the component B can be 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1.0, 100:1.1, etc.

[0043] The mass ratio of component A to component B can be (1.6-2.2):(0.6-1.1), that is, (1.45-3.7):1, for example, it can be 1.45:1, 1.55:1, 1.65:1, 1.75:1, 1.85:1, 1.95:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, etc.

[0044] In the present application, component B includes 20-75wt% of passivated microsilica powder, preferably 30-50wt%, preferably 45-60wt%, graphite powder 5-10wt%, zircon powder 5-20wt%, mullite particles 5-25wt%, and 1-10wt% of lignin sulfonate, preferably 5-10wt%.

[0045] In some embodiments, component B consists of 20-75 wt % of passivated microsilica powder, 5-10 wt % of graphite powder, 5-20 wt % of zircon powder, 5-25 wt % of mullite particles and 1-10 wt % of lignin sulfonate.

[0046] Furthermore, in component B, the mass fraction of the passivated microsilica powder is 40wt%-60wt%. The reaction rate of the passivated microsilica powder with the sodium silicate in component A is low, which can reduce the rate of increase of the modulus of the sodium silicate in the liquid component A, thereby maintaining the spherical structure of the powder material and the thin film water layer in the silica sand mixture, thereby strengthening the ball effect and improving the fluidity of the material.

[0047] In some embodiments, in component B, the mass fraction of the passivated microsilica powder is 45wt%-60wt%.

[0048] In some embodiments, in component B, the mass fraction of the passivated microsilica powder is 50wt%-60wt%.

[0049] In some embodiments, in component B, the mass fraction of the passivated microsilica powder is 30 wt%-50 wt%.

[0050] Specifically, in component B, the mass fraction of the passivated microsilica powder can be 20wt%, 20.5wt%, 21wt%, 21.5wt%, 22wt%, 22.5wt%, 23wt%, 23.5wt%, 24wt%, 24.5wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt %, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59 wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, etc.

[0051] In component B, the mass fraction of the graphite powder can be 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7. 4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7w t%, 8.8wt%, 8.9wt%, 9wt%, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, etc.

[0052] In component B, the mass fraction of the zircon powder can be 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt%, 8.9wt%, 9wt%, 9.1wt%, 9.2wt%, 9 .3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, 11wt%, 11 .5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt%, 15.5wt%, 16wt%, 16.5wt%, 17wt%, 17.5wt%, 18wt%, 18.5wt%, 19wt%, 19.5wt%, 20wt%, etc.

[0053] In component B, the mass fraction of the mullite particles can be 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt% , 8.9wt%, 9wt%, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9. 9wt%, 10wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt %, 15.5wt%, 16wt%, 16.5wt%, 17wt%, 17.5wt%, 18wt%, 18.5wt%, 19wt%, 19.5wt%, 20wt% , 20.5wt%, 21wt%, 21.5wt%, 22wt%, 22.5wt%, 23wt%, 23.5wt%, 24wt%, 24.5wt%, 25wt%, etc.

[0054] In some embodiments, in component B, the mass fraction of the lignin sulfonate is 5wt-10wt.

[0055] In some embodiments, in component B, the mass fraction of the lignin sulfonate is 5wt-8wt.

[0056] Specifically, in component B, the mass fraction of the lignin sulfonate can be 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%. , 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt% , 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5wt%, 5.1wt%, 5.2wt%, 5.3wt %, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5 wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7. 7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt%, 8 .9wt%, 9wt%, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, etc.

[0057] In the present application, the lignin sulfonate is one of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate.

[0058] The mullite particles are artificial sand spherical particles with an aluminum oxide content of greater than or equal to 60wt%.

[0059] In the present application, the D50 particle size of the mullite particles is 30-100 μm, preferably 30-50 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc.

[0060] The D50 particle size of the graphite powder is 30-100 μm, preferably 30-50 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc.

[0061] The D50 particle size of the zircon powder is 30-100 μm, preferably 30-50 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc.

[0062] The D50 particle size of each component in component B can better fill the tiny gaps between silica sands, thereby improving the density and uniformity of the mixture, providing better active sites for chemical reactions, and enhancing the realization of the ball effect.

[0063] In this application, "particle size" is also called "particle size" or "diameter". When a certain physical property or physical behavior of the measured particle is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size (or particle size distribution) of the measured particle. The particle size is generally divided into a single particle size representing the size of a single particle and an average particle size representing a particle group composed of particles of different sizes. Since the shape of actual particles is usually non-spherical, it is difficult to directly express their size with a diameter. Therefore, in the field of particle size testing, for non-spherical particles, the particle size is usually characterized by an equivalent particle size (generally referred to as particle size). The equivalent particle size means that when the physical property or physical behavior of a particle is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size of the measured particle. In this application, the D50 particle size refers to the particle size corresponding to the volume cumulative particle size distribution percentage of a sample reaching 50%. Its physical meaning is that particles with a diameter larger than it account for 50%, and particles with a diameter smaller than it also account for 50%. D50 is also called the median diameter or median particle size.

[0064] The D50 particle size was determined using a Malvern Mastersizer 3000 particle size analyzer.

[0065] In the present application, the D50 particle size of the passivated microsilica powder is 5-100μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 10-75μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 10-70μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 30-80μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 30-50μm, for example, it can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, etc.

[0066] The specific surface area of ​​the passivated microsilica powder is 0.1-2m 2 / g, for example, 0.1m 2 / g, 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2m 2 / g, etc.

[0067] The mass fraction of silicon dioxide in the passivated microsilica powder is 90-99wt%, for example, it can be 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99wt%, etc.

[0068] When preparing the warm core box, microsilica powder has two functions. On the one hand, it can undergo a polymerization reaction with the sodium silicate in the liquid component to form a complex three-dimensional network structure, thereby promoting solidification and increasing strength; on the other hand, it has a spherical structure, which can change the sliding friction between the sand particles into rolling friction, thereby achieving a ball effect to increase fluidity. However, the reaction speed of microsilica powder is too fast, which will rapidly increase the modulus of water glass, form Si-O-Si bonds, and enhance cohesive strength, thereby inhibiting the ball effect of its spherical structure. Passivated microsilica powder can reduce the reaction rate by 35% due to its larger particle size, fewer surface hydroxyl groups, and weaker activity, thereby better exerting the above two functions, thereby improving the fluidity of the silica sand mixture.

[0069] In this article, the passivated microsilica powder can be used as long as it can reduce the reaction rate and thus improve the fluidity of the silica sand mixture. In a specific example, microsilica powder with a particle size of 5-100 μm can be used. In a specific example, microsilica powder with a specific surface area of ​​0.1-2 m 2 / g of microsilica powder. In a specific example, microsilica powder with a silicon dioxide content of 90-99wt% can be used. In a specific example, microsilica powder with a specific surface area of ​​0.1-2m 2 / g, and a silicon dioxide content of 90-99wt%. In a specific example, a particle size of 5-100μm and a specific surface area of ​​0.1-2m 2 / g of microsilica powder, in a specific example, a particle size of 5-100 μm and a silicon dioxide content of 90-99 wt% can be used. In a specific example, a particle size of 5-100 μm and a specific surface area of ​​0.1-2 m 2 / g, microsilica powder with a silicon dioxide content of 90-99wt%.

[0070] In the present application, component A includes 25-40wt% sodium silicate, 0.5-2wt% potassium hydroxide, 0.5-2wt% sodium aluminate, 2-10wt% silica sol, and the balance is deionized water.

[0071] Specifically, in component A, the mass fraction of sodium silicate can be 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt% and the like.

[0072] In component A, the mass fraction of potassium hydroxide can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, etc.

[0073] In component A, the mass fraction of sodium aluminate can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, etc.

[0074] In component A, the mass fraction of the silica sol can be 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5 .9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9w t%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt%, 8.9wt%, 9wt %, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, etc.

[0075] The present application provides a method for preparing the aforementioned inorganic warm core box, comprising the following steps:

[0076] Put 100 parts by weight of silica sand into a sand mixer, add a certain proportion of binder component A and binder component B, mix, and put the mixed molding sand into the sand shooting bucket of a core shooting machine to make cores.

[0077] In the preparation method, the specific composition and parameters of component A and component B can refer to the above description.

[0078] The present application provides a binder, comprising component A and component B, wherein component A comprises 25-40wt% of sodium silicate, 0.5-2wt% of potassium hydroxide, 0.5-2wt% of sodium aluminate, 2-10wt% of silica sol, and the balance is deionized water; component B comprises 20-75wt% of passivated microsilica powder, preferably 30-50wt%, preferably 45-60wt%, 5-10wt% of graphite powder, 5-20wt% of zircon powder, 5-25wt% of mullite particles, and 1-10wt% of lignin sulfonate, preferably 5-10wt%.

[0079] The present application provides a binder, which consists of component A and component B. Component A consists of 25-40wt% sodium silicate, 0.5-2wt% potassium hydroxide, 0.5-2wt% sodium aluminate, 2-10wt% silica sol, and the balance is deionized water; component B consists of 20-75wt% passivated microsilica powder, 5-10wt% graphite powder, 5-20wt% zircon powder, 5-25wt% mullite particles and 1-10wt% lignin sulfonate.

[0080] Component A is a liquid component, and component B is a powder component.

[0081] The main component of the liquid component is sodium silicate, which dehydrates and hardens during the hot air blowing process, playing the main bonding role. The powder component reacts with the liquid binder to increase the modulus of the binder, thereby promoting hardening and improving the strength of the sand core; at the same time, the spherical structure of the powder material can achieve a ball effect, promote the sliding of sand particles, reduce solid friction, and thus improve the fluidity of the silica sand mixture.

[0082] In the present application, the mass ratio of component A to component B can be any value and can be specifically set according to actual needs. For example, when the binder is used to prepare a warm core box, the raw materials of the warm core box include silica sand in addition to components A and B. The added amount of component A is 1.6%-2.2% of the mass of the silica sand, and the added amount of component B is 0.6%-1.1% of the mass of the silica sand. Then the mass ratio of component A to component B is (1.6-2.2):(0.6-1.1).

[0083] Specifically, in component A, the mass fraction of sodium silicate can be 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt% and the like.

[0084] In component A, the mass fraction of potassium hydroxide can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, etc.

[0085] In component A, the mass fraction of sodium aluminate can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, etc.

[0086] In component A, the mass fraction of the silica sol can be 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5 .9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9w t%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt%, 8.9wt%, 9wt %, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, etc.

[0087] In some embodiments, in component B, the mass fraction of the passivated microsilica powder is 40wt%-60wt%. The reaction rate of the passivated microsilica powder with the sodium silicate in component A is low, which can reduce the rate of increase of the modulus of the sodium silicate in the liquid component A, thereby maintaining the spherical structure of the powder material and the thin film water layer in the silica sand mixture, thereby strengthening the ball effect and improving the fluidity of the material.

[0088] In some embodiments, in component B, the mass fraction of the passivated microsilica powder is 45wt%-60wt%.

[0089] In some embodiments, in component B, the mass fraction of the passivated microsilica powder is 50wt%-60wt%.

[0090] In some embodiments, in component B, the mass fraction of the passivated microsilica powder is 30 wt%-50 wt%.

[0091] Specifically, in component B, the mass fraction of the passivated microsilica powder can be 20wt%, 20.5wt%, 21wt%, 21.5wt%, 22wt%, 22.5wt%, 23wt%, 23.5wt%, 24wt%, 24.5wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36wt%, 37wt%, 38wt%, 39wt%, 40wt%, 41wt%, 42wt %, 43wt%, 44wt%, 45wt%, 46wt%, 47wt%, 48wt%, 49wt%, 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59 wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt%, 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, etc.

[0092] In component B, the mass fraction of the graphite powder can be 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7. 4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7w t%, 8.8wt%, 8.9wt%, 9wt%, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, etc.

[0093] In component B, the mass fraction of the zircon powder can be 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt%, 8.9wt%, 9wt%, 9.1wt%, 9.2wt%, 9 .3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, 11wt%, 11 .5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt%, 15.5wt%, 16wt%, 16.5wt%, 17wt%, 17.5wt%, 18wt%, 18.5wt%, 19wt%, 19.5wt%, 20wt%, etc.

[0094] In component B, the mass fraction of the mullite particles can be 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7.7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt% , 8.9wt%, 9wt%, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9. 9wt%, 10wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt %, 15.5wt%, 16wt%, 16.5wt%, 17wt%, 17.5wt%, 18wt%, 18.5wt%, 19wt%, 19.5wt%, 20wt% , 20.5wt%, 21wt%, 21.5wt%, 22wt%, 22.5wt%, 23wt%, 23.5wt%, 24wt%, 24.5wt%, 25wt%, etc.

[0095] In some embodiments, in component B, the mass fraction of the lignin sulfonate is 5wt-10wt.

[0096] In some embodiments, in component B, the mass fraction of the lignin sulfonate is 5wt-8wt.

[0097] Specifically, in component B, the mass fraction of the lignin sulfonate can be 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%. , 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt% , 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5wt%, 5.1wt%, 5.2wt%, 5.3wt %, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5 wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%, 7.1wt%, 7.2wt%, 7.3wt%, 7.4wt%, 7.5wt%, 7.6wt%, 7. 7wt%, 7.8wt%, 7.9wt%, 8wt%, 8.1wt%, 8.2wt%, 8.3wt%, 8.4wt%, 8.5wt%, 8.6wt%, 8.7wt%, 8.8wt%, 8 .9wt%, 9wt%, 9.1wt%, 9.2wt%, 9.3wt%, 9.4wt%, 9.5wt%, 9.6wt%, 9.7wt%, 9.8wt%, 9.9wt%, 10wt%, etc.

[0098] In the present application, the lignin sulfonate is one of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate.

[0099] The mullite particles are artificial sand spherical particles with an aluminum oxide content of greater than or equal to 60wt%.

[0100] In the present application, the D50 particle size of the mullite particles is 30-100 μm, preferably 30-50 μm. For example, it can be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm,

[0101] 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, etc.

[0102] The D50 particle size of the graphite powder is 30-100 μm, preferably 30-50 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc.

[0103] The D50 particle size of the zircon powder is 30-100 μm, preferably 30-50 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc.

[0104] The D50 particle size of each component in component B can better fill the tiny gaps between silica sands, thereby improving the density and uniformity of the mixture, providing better active sites for chemical reactions, and enhancing the realization of the ball effect.

[0105] "Particle size" is also called "particle size" or "diameter". When a certain physical property or physical behavior of the measured particle is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size (or particle size distribution) of the measured particle. Particle size is generally divided into a single particle size representing the size of a single particle and an average particle size representing a particle group composed of particles of different sizes. Since the shape of actual particles is usually non-spherical, it is difficult to directly express their size with a diameter. Therefore, in the field of particle size testing, for non-spherical particles, the particle size is usually characterized by an equivalent particle size (generally referred to as particle size). Equivalent particle size means that when a particle's physical property or physical behavior is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size of the measured particle. In this application, D50 particle size refers to the particle size corresponding to the volume cumulative particle size distribution percentage of a sample reaching 50%. Its physical meaning is that particles with a diameter larger than it account for 50%, and particles with a diameter smaller than it also account for 50%. D50 is also called the median diameter or median particle size.

[0106] The D50 particle size was determined using a Malvern Mastersizer 3000 particle size analyzer.

[0107] In the present application, the D50 particle size of the passivated microsilica powder is 5-100μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 10-75μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 10-70μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 30-80μm. In some embodiments, the D50 particle size of the passivated microsilica powder is 30-50μm, for example, it can be 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, etc.

[0108] The specific surface area of ​​the passivated microsilica powder is 0.1-2m 2 / g, for example, 0.1m 2 / g, 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2m 2 / g, etc.

[0109] The mass fraction of silicon dioxide in the passivated microsilica powder is 90-99wt%, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%,

[0110] 98wt%, 99wt%, etc.

[0111] When preparing the warm core box, microsilica powder has two functions. On the one hand, it can undergo a polymerization reaction with the sodium silicate in the liquid component to form a complex three-dimensional network structure, thereby promoting solidification and increasing strength; on the other hand, it has a spherical structure, which can change the sliding friction between the sand particles into rolling friction, thereby achieving a ball effect to increase fluidity. However, the reaction speed of microsilica powder is too fast, which will rapidly increase the modulus of water glass, form Si-O-Si bonds, and enhance cohesive strength, thereby inhibiting the ball effect of its spherical structure. Passivated microsilica powder can reduce the reaction rate by 35% due to its larger particle size, fewer surface hydroxyl groups, and weaker activity, thereby better exerting the above two functions, thereby improving the fluidity of the silica sand mixture.

[0112] In the present application, the passivated microsilica powder is obtained by the following steps:

[0113] Step 1: adding an alkaline treatment liquid containing a dispersant to the microsilica powder and stirring to obtain a mixture;

[0114] Step 2: adding a certain amount of silane coupling agent to the mixture, and continuing to stir to obtain a mixed slurry;

[0115] Step three: filtering, drying and calcining the mixed slurry to obtain the passivated microsilica powder.

[0116] In step one, an alkaline treatment solution containing a dispersant is added to the microsilica powder, and the mixture is stirred at room temperature to obtain a mixture one. The mixture one is stirred mechanically at a high speed at 50-90° C. for 1-3 hours to obtain the mixture.

[0117] Specifically, the stirring time at room temperature is 10-30 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc. The stirring rate is 1200 rpm-2000 rpm, for example, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm.

[0118] Herein, room temperature refers to any temperature between 15°C-30°C, for example, it may be 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc.

[0119] The stirring temperature of the mixture during high-speed mechanical stirring can be any temperature between 50°C and 90°C, for example, 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, 90°C, etc. The stirring time can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, etc.

[0120] The stirring rate during the high-speed mechanical stirring process is 1200rpm-2000rpm, for example, 1200rpm, 1400rpm, 1600rpm, 1800rpm, 2000rpm.

[0121] Specifically, the amount of alkaline treatment liquid added is 30-60 times the weight of microsilica powder. When the weight of microsilica powder is m, the amount of alkaline treatment liquid added is any value between 30m-60m, for example, it can be 30m, 32m, 34m, 36m, 38m, 40m, 42m, 44m, 46m, 48m, 50m, 52m, 54m, 56m, 58m, 60m, etc.

[0122] The solute of the alkaline treatment solution is one of sodium carbonate, sodium bicarbonate, potassium carbonate, and ammonium carbonate, and the amount of the solute added is 5-10% of the alkaline treatment solution, for example, 5%, 6%, 7%, 8%, 9%, 10%, etc. When the mass of the alkaline treatment solution is n, the amount of the solute added is any value between 0.05n-0.1n, for example, 0.05n, 0.06n, 0.07n, 0.08n, 0.09n, 0.1n, etc.

[0123] The dispersant is selected from one of polyethylene glycol 200, polyethylene glycol 400 and polyethylene glycol 600.

[0124] The amount of the dispersant added is 1-3% of the mass of the alkaline treatment liquid, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, etc. When the mass of the alkaline treatment liquid is n, the amount of the dispersant added is 0.01n, 0.015n, 0.02n, 0.025n, 0.03n, etc.

[0125] In step 2, a silane coupling agent is added to the mixture, and stirring is continued for 1-3 hours at a stirring rate of 1200 rpm-2000 rpm, for example, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, thereby obtaining a mixed slurry;

[0126] The silane coupling agent is selected from one of dimethyldiethoxysilane, trimethylethoxysilane, methyltriethoxysilane and vinyltriethoxysilane.

[0127] The amount of the silane coupling agent added is 2-5% of the mass of the microsilica powder, preferably 2-3%, for example, it can be 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% and the like.

[0128] In step three, the calcination temperature is 200-800° C., preferably 500-800° C., and the calcination time is 1-3 hours.

[0129] Specifically, the calcination temperature may be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.

[0130] The calcination time can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, etc.

[0131] The present application also provides a method for preparing the aforementioned binder, comprising the following steps:

[0132] Preparation of component A: Prepare component A according to a formula of 25-40wt% sodium silicate, 0.5-2wt% potassium hydroxide, 0.5-2wt% sodium aluminate, 2-10wt% silica sol and the balance being deionized water;

[0133] Preparation of component B: Prepare component B according to the formula of 20-75wt% of passivated microsilica powder, 5-10wt% of graphite powder, 5-20wt% of zircon powder, 5-25wt% of mullite particles and 1-10wt% of lignin sulfonate.

[0134] Specifically, the passivated microsilica powder is obtained by the following steps:

[0135] Step 1: adding an alkaline treatment liquid containing a dispersant to the microsilica powder and stirring to obtain a mixture;

[0136] Step 2: adding a certain amount of silane coupling agent to the mixture, and continuing to stir to obtain a mixed slurry;

[0137] Step three: filtering, drying and calcining the mixed slurry to obtain the passivated microsilica powder.

[0138] In step one, an alkaline treatment solution containing a dispersant is added to the microsilica powder, and the mixture is stirred at room temperature to obtain a mixture one. The mixture one is stirred mechanically at a high speed at 50-90° C. for 1-3 hours to obtain the mixture.

[0139] Specifically, the stirring time at room temperature is 10-30 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc. The stirring rate is 1200 rpm-2000 rpm, for example, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm.

[0140] Herein, room temperature refers to any temperature between 15°C-30°C, for example, it may be 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc.

[0141] The stirring temperature of the mixture during high-speed mechanical stirring can be any temperature between 50°C and 90°C, for example, 50°C, 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 85°C, 88°C, 90°C, etc. The stirring time can be 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, etc.

[0142] The stirring rate during the high-speed mechanical stirring process is 1200rpm-2000rpm, for example, 1200rpm, 1400rpm, 1600rpm, 1800rpm, 2000rpm.

[0143] Specifically, the amount of alkaline treatment liquid added is 30-60 times the weight of microsilica powder. When the weight of microsilica powder is m, the amount of alkaline treatment liquid added is any value between 30m-60m, for example, it can be 30m, 32m, 34m, 36m, 38m, 40m, 42m, 44m, 46m, 48m, 50m, 52m, 54m, 56m, 58m, 60m, etc.

[0144] The solute of the alkaline treatment solution is one of sodium carbonate, sodium bicarbonate, potassium carbonate, and ammonium carbonate, and the amount of the solute added is 5-10% of the alkaline treatment solution, for example, 5%, 6%, 7%, 8%, 9%, 10%, etc. When the mass of the alkaline treatment solution is n, the amount of the solute added is any value between 0.05n-0.1n, for example, 0.05n, 0.06n, 0.07n, 0.08n, 0.09n, 0.1n, etc.

[0145] The dispersant is selected from one of polyethylene glycol 200, polyethylene glycol 400 and polyethylene glycol 600.

[0146] The amount of the dispersant added is 1-3% of the mass of the alkaline treatment liquid, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9wt%, 3wt%, etc. When the mass of the alkaline treatment liquid is n, the amount of the dispersant added is 0.01n, 0.015n, 0.02n, 0.025n, 0.03n, etc.

[0147] In step 2, a silane coupling agent is added to the mixture, and stirring is continued for 1-3 hours, with a stirring rate of 1200 rpm-2000 rpm, for example, 1200 rpm, 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, to obtain a mixed slurry;

[0148] The silane coupling agent is selected from one of dimethyldiethoxysilane, trimethylethoxysilane, methyltriethoxysilane and vinyltriethoxysilane.

[0149] The added amount of the silane coupling agent is 2-5% of the mass of the microsilica powder, for example, it can be 2%, 3%, 4%, 5%, etc.

[0150] In step three, the calcination temperature is 200-800° C. and the calcination time is 1-2 hours.

[0151] Specifically, the calcination temperature may be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc.

[0152] The calcination time can be 1 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2 h, etc.

[0153] The binder described in the present application, when preparing sand molds, component B can effectively improve the fluidity of the mixture of silica sand and binder. The improvement of fluidity can improve the stability and compactness of the sand mold surface, can improve the core making effect of complex sand cores; can increase the surface finish and dimensional accuracy of castings, reduce inclusions, pores, sand holes and other problems, thereby improving the production efficiency of castings and the economic benefits of foundries.

[0154] The spherical structure of the B component of the binder of the present application can achieve a ball effect, which can change the sliding friction between sand particles into rolling friction between sand particles and spherical particles, reduce solid friction, and reduce the viscosity and friction resistance of the binder and silica sand mixture, thereby effectively improving its fluidity. In the hammer fluidity test, the fluidity value can be increased by about 50% compared with similar binders.

[0155] Example

[0156] The experimental methods used in the following examples are all conventional methods unless otherwise specified.

[0157] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0158] Example 1

[0159] The method for preparing the high-fluidity inorganic warm core box of this embodiment comprises the following steps:

[0160] The amount of liquid A component added is 1.6% of the weight of silica sand; the amount of powder B component added is 0.8% of the weight of silica sand. Put 100 parts of silica sand into the sand mixer, add a certain proportion of liquid component and powder component, mix for 3 minutes, put the mixed molding sand into the sand shooting hopper of the core shooting machine to prepare for core making. The core making parameters are core box temperature 150℃, hot air temperature 200℃, blowing time 60s, and sand shooting pressure 0.5MPa.

[0161] The liquid component A includes the following components in mass percentage: 35wt% sodium silicate, 1wt% potassium hydroxide, 1wt% sodium aluminate, 10wt% silica sol, and 53wt% deionized water. The powder component B includes the following components in mass percentage: 50wt% passivated microsilica powder, 15wt% zircon powder, 10wt% mullite particles, 5wt% sodium lignin sulfonate, and the balance is graphite powder.

[0162] The preparation process of passivated microsilica powder in component B is as follows:

[0163] (1) adding 30 units of alkaline treatment solution to 1 unit of microsilica powder, wherein the alkaline treatment solution is a mixed solution of 5% sodium carbonate and 1% polyethylene glycol 200;

[0164] (2) The obtained mixture was mechanically stirred at room temperature for 10 min, and then stirred at 60° C. for 2 h.

[0165] (3) then adding 3% of dimethyldiethoxysilane based on the weight of the microsilica powder and continuing stirring for 2 hours;

[0166] (4) After filtering and drying the mixed slurry, it is calcined at 500°C for 3 hours to obtain a dry powder, namely, passivated microsilica powder.

[0167] The mullite particles are spherical particles of 50μm with an alumina content of 65%. The D50 particle size of the passivated microsilica powder is 50μm and the specific surface area is 0.78m 2 The content of silicon oxide in the passivated microsilica powder is 97%, the D50 particle size of the graphite powder is 80 μm, and the D50 particle size of the zircon powder is 50 μm.

[0168] The parameters of the inorganic temperature core box of this embodiment are shown in Table 1.

[0169] The difference between Example 2 to Example 4 and Comparative Example 1 to Comparative Example 2 and Example 1 is that the content of passivated microsilica powder is different, and other parameters are the same. The specific parameters are shown in Table 1.

[0170] The difference between Example 5 and Example 6 and Example 1 is that the sizes of the passivated microsilica powder are different, and the other parameters are the same. The specific parameters are shown in Table 1.

[0171] The difference between Example 7-Example 8 and Comparative Example 3-Comparative Example 4 and Example 1 is that the content of sodium lignin sulfonate is different, and other parameters are the same. The specific parameters are shown in Table 1.

[0172] The difference between Example 9 to Example 12 and Example 1 is that the sintering temperatures in the preparation process of passivated microsilica powder are different, and other parameters are the same. The specific parameters are shown in Table 1.

[0173] The difference between Example 13 to Example 17 and Example 1 is that the mass ratio of component A to component B is different, and other parameters are the same. The specific parameters are shown in Table 1.

[0174] The difference between Comparative Example 5 and Example 1 is that there is only component A but no component B, and other parameters are the same. The specific parameters are shown in Table 1.

[0175] The difference between Comparative Example 6 and Example 1 is that the microsilica powder is not passivated, and other parameters are the same. The specific parameters are shown in Table 1.

[0176] Hammer flowability test method to test:

[0177] Step (1) Weigh 1 kg of sand and a corresponding binder; pour the materials into a sand mixer, and start the mixer to obtain a uniform silica sand / binder mixture.

[0178] Step (2) Weigh 185 g of sand sample, pour it into a standard sample tube, and place the sample tube under the hammer-type sample making machine to scrape off the sand outside the side hole.

[0179] Step (3) impacts 10 times on the sample making machine, and weighs the total weight of the sand squeezed out from the lower side hole of the sample tube after impacting 10 times on a balance.

[0180] The total weight of the sand obtained corresponds to the fluidity value. The weight represents the fluidity. The greater the weight, the better the fluidity.

[0181] The bending strength is measured by the sand strength tester after the bending test block is punched out by the core shooting machine. The quality of the collapsibility can be obtained by observing the sand core residue in the casting cavity after pouring.

[0182] Table 1 shows the parameters of each embodiment and comparative example.

[0183]

[0184]

[0185] Summary: When preparing sand molds, the binder of the present application, component B can change the sliding friction between sand particles into rolling friction between sand particles and spherical particles, reduce solid friction, and reduce the viscosity and friction resistance of the binder and silica sand mixture, thereby effectively improving its fluidity (fluidity can reach 9.1g). The improvement in fluidity can improve the stability and compactness of the sand mold surface, improve the core making effect of complex sand cores, and increase the surface finish and dimensional accuracy of the casting.

[0186] Although the embodiments of the present application are described above, the present application is not limited to the above specific embodiments and application fields, and the above specific embodiments are merely illustrative and instructive, rather than restrictive. A person of ordinary skill in the art can make many forms under the guidance of this specification and without departing from the scope of protection of the claims of the present application, all of which belong to the protection of the present application.

Claims

1. An inorganic warm core box, comprising 100 parts (by weight percentage) of silica sand and 2.2-3.3 parts of a binder, wherein the binder comprises component A and component B, characterized in that: The B component comprises passivated silicon powder.

2. The inorganic warm core box according to claim 1, characterized in that: The mass ratio of the A component to the B component is (1.6-2.2):(0.6-1.1).

3. The inorganic warm core box according to claim 1, characterized in that: The particle size of the passivated microsilica powder is 5-100 μm, preferably 30-75 μm.

4. The inorganic warm core box according to claim 1, characterized in that: The specific surface area of ​​the passivated microsilica powder is 0.1-2m 2 / g.

5. The inorganic warm core box according to claim 1, characterized in that: The content of silicon dioxide in the passivated microsilica powder is 90-99wt%.

6. The inorganic warm core box according to claim 1, characterized in that: The B component comprises 20-75wt% of passivated microsilica powder, 5-10wt% of graphite powder, 5-20wt% of zircon powder, 5-25wt% of mullite particles and 1-10wt% of lignin sulfonate.

7. The inorganic warm core box according to claim 6, characterized in that: The lignin sulfonate is one of sodium lignin sulfonate, calcium lignin sulfonate and magnesium lignin sulfonate; or The mullite particles are artificial sand spherical particles with an aluminum oxide content of greater than or equal to 60wt%.

8. A method for preparing the inorganic warm core box according to any one of claims 1 to 7, characterized in that: The steps include: Put 100 parts by weight of silica sand into a sand mixer, add a certain proportion of binder component A and binder component B, mix, and put the mixed molding sand into the sand shooting bucket of a core shooting machine to make cores.

9. A binder, characterized in that: The invention comprises component A and component B, wherein the component B comprises passivated silicon powder.

10. A method for preparing a binder, characterized in that: The steps include: Preparation of component A: Prepare component A according to a formula of 25-40wt% sodium silicate, 0.5-2wt% potassium hydroxide, 0.5-2wt% sodium aluminate, 2-10wt% silica sol and the balance being deionized water; Preparation of component B: Prepare component B according to the formula of 20-75wt% of passivated microsilica powder, 5-10wt% of graphite powder, 5-20wt% of zircon powder, 5-25wt% of mullite particles and 1-10wt% of lignin sulfonate.

Citation Information

Patent Citations

  • Modified silicate-bonded sand temperature core box core-producing technique

    CN100531959C

  • A curing agent for casting water glass

    CN108393430B

  • Warm core box binder and preparation method thereof

    CN114406181A

  • Modified silicate-bonded sand temperature core box core-producing technique

    CN101172302A

  • Two-component system, in particular for forming an adhesive

    CN105848804A